Semiotic and Implication of Hijab toward Da’wah in Indonesia - Kumala, Nur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
Subjectivity of meaning is inseparable from human interpretation, as exemplified in the case of the hijab. This research employed a quantitative method combined with a semiotic approach, specifically utilizing Roland Barthes' semiotics framework, comprising three levels: denotation, connotation, and myth deconstruction. The study focused on the interpretation of QS. Al-Ahzab: 59 and connotative practices embedded in societal social behaviors. The results of research indicated that the association of wearing the headscarf with the standardization of women's religiosity is a constructed myth. It further revealed that this myth becomes an ideology when it legitimizes a single interpretation and invalidates other meanings. For instance, the perception that a shalihah (pious) woman is defined solely by wearing a hijab or that a longer veil indicates greater piety contrasts with the principles of Islam. These principles emphasize promoting goodness and avoiding harm (jalbul mashalih-dar'ul mafasid), advocating non-coercion, and preaching with kindness (amar ma'ruf nahi munkar bil ma'ruf). This study contributes to the scholarly understanding of the intersection between religious texts and social practices by uncovering how ideological myths influence the interpretation and application of religious symbols in daily life. It provides a methodological model for examining the role of semiotics in deconstructing entrenched societal norms and offers insights into the potential misuse of religious symbolism in shaping societal ideologies